Journalistic Message: Spur of the Moment Artifacts or Spontaneity Creative Work - Kulevski, Tsvetan (Research Papers, 2009)
In this article is making a detailed theoretic-logical analysis to form journalistic message as succession on the spur of the moment artifacts. In its quality thought reflection of reality it proves that they put the root of one in a peculiar manner “creative spur of the moment” which is the main body of the entirety journalistic process.